ナンキョク チイキ カイガンセン フキン ノ ロガン チタイ ノ イケ オヨビ フウカブツ ニツイテ - 目黒, 煕; メグロ, ヒロシ; MEGURO, Hiroshi (国立極地研究所, 1962)
P(論文) On the coastal region of Antarctica (from 39°E to 49°E) many ponds and pools are found on bare rocks during the summer. Limnological observations of these ponds and pools were carried out in four places. The water is considered to originate in melted snow. The temperature of the surface water ranged between 1℃ and 14℃ by solar radiation. This is intersting considering the fact that the air temperature was below 5℃. Some algae were found on the bottom. Nutrient salts are very poor; traces of P0_3, N0_2, NH_3 were detected. Si0_2 is 20-30 mμ/1. Dissolved oxygen is 7-9 cc/1 and saturated at this temperature. On the coast of Rena Bay (67°20'S, 49°15'E) a small amount of soil was found near a glacier. departmental bulletin paper